How do the existing homecare services correspond with the preferred service ecosystem for senior citizens living at home? A qualitative interview study with multiple stakeholders - Kattouw, Christophe Eward; Aase, Karina; Viksveen, Petter (Frontiers in Health Services, 2024)
Introduction Often, homecare services are task-focused rather than person-based and fragmented instead of integrated. Consequently, several stakeholders have requested a transformation of the service ecosystem for senior citizens living at home. This transformation may be facilitated by an idealized design approach. However, few studies have applied such an approach. Moreover, previous research did not assess the ways in which the existing homecare services correspond with the preferred service ecosystem for senior citizens living at home. Therefore, the purpose of this study is to gain an understanding of how the existing homecare services correspond with the preferred service ecosystem for senior citizens living at home, according to different stakeholders. Methods Four stakeholder groups (n = 57) from a Norwegian municipality participated in an interview study (2019–2020): senior citizens, carers, healthcare professionals and managers. A directed qualitative content analysis was applied, guided by a four-category framework for the preferred service ecosystem. Results All stakeholder groups highlighted several limitations that hindered continuity of the services. There was also agreement on deficiencies in professionals’ competence, yet professionals themselves did not focus on this as a significant aspect. Managers emphasised the importance of professionals’ reablement competence, which was also considered to be deficient in the current homecare services. Contrary to the other stakeholder groups, most senior citizens seemed satisfied with the practical and social support they received. Together with carers, they also explained why they thought some professionals lack compassion. Their dependency on professionals may limit them in sharing honestly their opinions and preferences during care provision. Involvement of senior citizens in improvement of the current services was limited. Insufficient time and resources, as well as a complex organisation impacted the existing homecare services, and therefore served as barriers to the preferred service ecosystem. Discussion In this study there were different degrees of correspondence between the existing homecare services and the preferred service ecosystem according to four stakeholder groups. To develop the preferred service ecosystem, aspects such as predictability, adaptivity, and relationships are key, as well as continuous involvement of senior citizens and other stakeholders. The four-category framework applied in this study served as a tool to assess the existing homecare services.